A Handbook of Economic Anthropology, Second Edition: Orientations: Karl Polanyi - Isaac, Barry L. (A Handbook of Economic Anthropology, Second Edition, 2012)
Anthropology
Keywords: capitalist systems; economic anthropology; economic history; economic sociology; history of economic thought: individuals; political economy; social and economic stratification

Understanding the “economization” of social formations - Jessop, Bob (The marketization of society: economizing the non-economic - Editors - Uwe Schimank, Ute Volkmann, 2012)
A critical review of nine dimensions of economization of social relations and their repercussions on societal dynamics. Discusses fictitious commodification, financialization, finance-dominated accumulation, and issues of ecological dominance. Bibliographic note: Book contains selected papers from conference on Marketization of Societies, organized at Bremen University, 1-2 June 2012. This is the pre-print version of a planned conference collection with a commercial publisher.
Sociology
Keywords: fictitious commodification; fictitious commodities; financialization

Neoliberalism through the Lens of 'Embeddedness' - Paton, Joy (Neoliberalism: Beyond the Free Market, 2012)
Political Science
Keywords: capitalist systems; history of economic thought: individuals; history of economic thought: macroeconomics; political economy

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
History; Sociology
Keywords: capitalisme; commerce; marché